2011
DOI: 10.1037/a0019949
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effects of adaptation on the perception of familiar faces.

Abstract: Figural aftereffects are commonly believed to be transient and to fade away in the course of milliseconds. We tested face aftereffects using familiar faces and found sustained effects lasting up to 1 week. In 3 experiments, participants were first exposed to distorted pictures of famous persons and then had to select the veridical face in a 2-alternative forced choice task. Veridicality aftereffects were found in a direction opposite to the adapting distortion; these effects generalized to other pictures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(111 citation statements)
references
References 66 publications
8
103
0
Order By: Relevance
“…Although there are 'de-adaptation' studies that employ a strategy of using an opposing stimulus to generate after-effects to counter-act those from the first stimulus (Mesik et al, 2013), it is not known whether even brief introduction of other face stimuli in the period between the adaptor and test stimuli affects the dynamics of the face after-effect. However, notwithstanding the findings from studies of long-term after-effects (Carbon and Ditye, 2011;Carbon et al, 2007), it is plausible that the effects of adaptation to one face would be altered and possibly reduced by viewing of another face. The goal of this study was to test the hypothesis that face identity after-effects would be reduced by exposure to other face stimuli.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although there are 'de-adaptation' studies that employ a strategy of using an opposing stimulus to generate after-effects to counter-act those from the first stimulus (Mesik et al, 2013), it is not known whether even brief introduction of other face stimuli in the period between the adaptor and test stimuli affects the dynamics of the face after-effect. However, notwithstanding the findings from studies of long-term after-effects (Carbon and Ditye, 2011;Carbon et al, 2007), it is plausible that the effects of adaptation to one face would be altered and possibly reduced by viewing of another face. The goal of this study was to test the hypothesis that face identity after-effects would be reduced by exposure to other face stimuli.…”
Section: Introductionmentioning
confidence: 90%
“…Recent studies also show a rapid decline in face identity after-effects in the first few seconds after adaptation (Leopold et al, 2001;Leopold et al, 2005;Rhodes et al, 2007). On the other hand, there are also reports that face distortion after-effects may persist at a modest level for 1 to 7 days (Carbon and Ditye, 2011;Carbon et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, low-level adaptation effects cannot explain all of the results that were found, because there was still less adaptation to participants' own faces than to famous or unfamiliar faces. Incidentally, the fact that physically identical face images gave rise to different amounts of adaptation in experiment 2, depending on whether or not the face belonged to the participant, represents further strong evidence that face-adaptation effects involve more than just adaptation to low-level image properties (see also Carbon and Ditye 2010;Hills et al 2010;Hole 2011).…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that figural aftereffects for familiar faces are significantly influenced by the identity of the face. More recently, Carbon and Ditye (2010) have shown that, whereas figural aftereffects for unfamiliar faces are generally reported to be quite shortlived, comparable aftereffects for familiar (famous) faces are much more long-lasting, being detectable as long as a week after adaptation first took place.…”
Section: Introductionmentioning
confidence: 99%